The Cell Biology of Tau Secretion - Merezhko, Maria; Uronen, Riikka-Liisa; Huttunen, Henri J. (Frontiers in Molecular Neuroscience, 2020)
The progressive accumulation and spread of misfolded tau protein in the nervous system is the hallmark of tauopathies, progressive neurodegenerative diseases with only symptomatic treatments available. A growing body of evidence suggests that spreading of tau pathology can occur via cell-to-cell transfer involving secretion and internalization of pathological forms of tau protein followed by templated misfolding of normal tau in recipient cells. Several studies have addressed the cell biological mechanisms of tau secretion. It now appears that instead of a single mechanism, cells can secrete tau via three coexisting pathways: (1) translocation through the plasma membrane; (2) membranous organelles-based secretion; and (3) ectosomal shedding. The relative importance of these pathways in the secretion of normal and pathological tau is still elusive, though. Moreover, glial cells contribute to tau propagation, and the involvement of different cell types, as well as different secretion pathways, complicates the understanding of prion-like propagation of tauopathy. One of the important regulators of tau secretion in neuronal activity, but its mechanistic connection to tau secretion remains unclear and may involve all three secretion pathways of tau. This review article summarizes recent advancements in the field of tau secretion with an emphasis on cell biological aspects of the secretion process and discusses the role of neuronal activity and glial cells in the spread of pathological forms of tau.